Palladium-catalyzed alpha-arylation of oxindoles. - Durbin, M; Willis, M (2008)
A catalyst generated from Pd(dba)2 and the bulky electron-rich phosphine ligand 2-(dicyclohexylphosphino)-2',4', 6'-tri-i-propyl-1-1'-biphenyl is effective for the alpha-arylation of oxindoles. Generation of the potassium-enolates of a range of oxindoles allows coupling with aryl chlorides, bromides, and triflates. Significant variation of the substitution pattern on both the oxindole and aryl halide is possible.